Development of the nephrotic syndrome during treatment of Crohn's disease with adalimumab - Gupta, Alok; Pendyala, Prashant; Arora, Pradeep; Sitrin, Michael D (Journal of clinical gastroenterology, 2011)
We report a patient with Crohn's disease who presented with renal insufficiency and the nephrotic syndrome after initiating therapy with adalimumab. Renal biopsy showed stages 2 to 3 membranous glomerulonephritis, and immunostaining showed glomerular deposition of immunoglobulin G and C3. The patient's serum creatinine decreased after discontinuation of adalimumab, and treatment with prednisone and mycophenolic acid reversed his proteinuria. The pathogenesis of glomerular disease induced by antitumor necrosis factor antibodies is uncertain, and the potential roles of the generation of autoantibodies, development of antiadalimumab antibodies, and the interaction of adalimumab with glomerular tumor necrosis factor are discussed.